Biomechanical Characterization of Preparation for Airs above the Ground: A Mixed Approach - Sophie Biau; Marine Leblanc; Eléna Pycik; Benoît Pasquiet; Benoit Huet (Animals, 2024)
Equitation in the French tradition is a school of riding that emphasizes harmonious relations between humans and horses. The best-known community is the Cadre Noir of Saumur, whose specialty is the air above the ground (AAG). No study has yet looked at the horse–rider interaction in this specific context. The purpose of this study was to identify and quantify indicators of AAGs based on the empirical perception of the écuyers expressed by a method of self-confrontation interviews. Fourteen training sessions were the subject of phenomenological and biomechanical approaches. Contact, balance, and hoof-beat, decisive for performance quality, were characterized for 49 AAGs, performed by five horses trained by two expert écuyers, with rein tension meters integrated in their double bridle (curb and snaffle reins) and six inertial measurement units fixed on the limbs, sternum, and croup. Their action was characterized by a peak of 65 ± 39 N on the inside curb rein. They considered that their horse was in balance (forehand inclined 13 ± 7° and −12 ± 9° for the hind hand). After the peak, during the 3.3 ± 2 s the horse’s trunk was stable and the écuyers released the contact until the AAG was perceived as satisfactory by the écuyer. The mixed approach allowed a pattern of action to be envisaged for the écuyer based on contact, balance, and hoof-beat in the execution of AAGs. The quantification of rein tension, trunk movements, and acceleration of the four limbs objectified the expert écuyers’ feeling of developing aptitudes for their actions in the human–horse interactions for improved transmission to young écuyers. The mixed approach used in this study has given rise to new training methods that are transferable to other equestrian activities.